2014
DOI: 10.1002/cne.23622
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and wiring variability of visual local neurons in the Drosophila medulla M6 stratum

Abstract: Local neurons in the vertebrate retina are instrumental in transforming visual inputs to extract contrast, motion, and color information and in shaping bipolar-to-ganglion cell transmission to the brain. In Drosophila, UV vision is represented by R7 inner photoreceptor neurons that project to the medulla M6 stratum, with relatively little known of this downstream substrate. Here, using R7 terminals as references, we generated a 3D volume model of the M6 stratum, which revealed a retinotopic map for UV represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 69 publications
2
21
0
Order By: Relevance
“…We found that the typical layer-specific targeting of R7 (to layer M6) and R8 (to M3) observed across the medulla 19 is different in DRA columns, where both R7 and R8 terminate in M6, with one cell always terminating slightly more distally ( Figure 1D). In agreement with previous reports 32 , we found that this layer targeting pattern could be ectopically induced by transforming all ommatidia into the DRA fate in flies via overexpression of the transcription factor Homothorax in all photoreceptors (GMR-Hth) 26,43 , ( Figure 1E). Quantification of the distance between R7 and R8 terminals in the medulla revealed a sharp boundary between DRA-specific and non-DRA layer targeting of inner photoreceptor cells ( Figure 1F).…”
Section: Presynaptic Properties Of Dra Inner Photoreceptors R7 and R8supporting
confidence: 93%
See 1 more Smart Citation
“…We found that the typical layer-specific targeting of R7 (to layer M6) and R8 (to M3) observed across the medulla 19 is different in DRA columns, where both R7 and R8 terminate in M6, with one cell always terminating slightly more distally ( Figure 1D). In agreement with previous reports 32 , we found that this layer targeting pattern could be ectopically induced by transforming all ommatidia into the DRA fate in flies via overexpression of the transcription factor Homothorax in all photoreceptors (GMR-Hth) 26,43 , ( Figure 1E). Quantification of the distance between R7 and R8 terminals in the medulla revealed a sharp boundary between DRA-specific and non-DRA layer targeting of inner photoreceptor cells ( Figure 1F).…”
Section: Presynaptic Properties Of Dra Inner Photoreceptors R7 and R8supporting
confidence: 93%
“…Interestingly, R8 cells in DRA ommatidia (here referred to as DRA.R8) resemble R7 cells in that they express an R7 Rhodopsin (Rh3), and down-regulate the crucial R8-specific transcription factor Senseless (Sens) around mid-pupation 26,31 . Furthermore, only in the DRA, R8 axons target to the deeper medulla layer M6, known to be the R7 target layer across the medulla 32 , whereas non-DRA R8 always terminate in layer M3 19 . Differences in layer targeting are known to be crucial for correct synaptic partner choice by photoreceptors 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Although X. peckii shows some preference for UV light, which is likely to be mediated by the UV-sensitive of one of the two Opsins found in the genome [67], it might only have basic color vision. Another reduction in connectivity can be observed in the fly medulla: While in the main eye, R7 and R8, the inner photoreceptors responsible for color detection, project to two different layers in the medulla (M6 and M3), the synapses collapse to one layer (M6) for monochromatic photoreceptors located in the dorsal rim area (DRA) [68] where the orientation of the vector of polarized light rather than colors is processed.…”
Section: Color Vision In Different Insectsmentioning
confidence: 99%
“…The medulla neuropil is organized in repetitive columnar units, oriented perpendicular to the ten layers that are reminiscent of lamina cartridges (Fischbach and Dittrich 1989). Retinotopic connections between medulla columns, photoreceptors and lamina cartridges ensure an accurate representation of the visual world (Fischbach and Dittrich 1989, Meinertzhagen and Sorra 2001, Morante and Desplan 2008, Zhu 2013, Chin et al 2014). …”
Section: The Drosophila Visual Systemmentioning
confidence: 99%